Cesarean Section for a Woman with Partial Transverse Vaginal Septum First Recognized in Early Labor: Case Report - Tegene, Dereje; Adisu, Getachew; Mohammed, Abduselam (Ethiopian Journal of Reproductive Health, 2022)
Background: Transverse vaginal septum is among the rarest form of female genital tract anomaly that arise from faulty canalization of the urogenital sinus and mullerian ducts. The clinical presentation and time of diagnosis depends on whether the septum is perforated or not. Some women with partial transverse vaginal septum are asymptomatic until first diagnosed during pregnancy or in labor. Case presentation: This is a 19 years old primigravida lady, come with pushing down pain of 3 hours at 40+1 weeks. Her antenatal care follow up was uneventful. She had no dyspareunia. Up on pelvic examination there was transverse vaginal septum with 1cm central opening. She gave birth by cesarean section. Conclusion: Cesarean section in early labor is a reasonable management option for women with transverse vaginal septum first recognized in early labor.